SERVICE QUALITY ANALYSIS IN A FREIGHT FORWARDING SERVICE IN JAKARTA USING SERVQUAL AND IMPORTANCE PERFORMANCE METHOD - Innisa, Deana Rohali; Purwanto, Agustinus Hariadi Djoko (International Humanities and Applied Science Journal, 2025)
Abstract – This study was motivated by sales’ volume decline of imported cargo and customers number of a shipping company in Jakarta (PT.BX) in the last two years. This contradicted with the Ministry of Trade data showing imports increases in that period. Countermeasures have been taken through priced reduction, nevertheless, complaints persist and the decline continues. This quantitative research applied statistical descriptive technique using ServQual and Importance Performance Analysis (IPA) tools. Questionnaire was prepared based on five ServQual dimensions (tangible, reliability, responsiveness, assurance, empathy) detailed to be 25 indicators from which 31 respondents (customers) provided their feedbacks. The reliability test shows that each dimension has a Cronbach alpha above 0.6, indicating that the instrument produces consistent and stable results, making the data reliable. The results of this research showed negative gaps in all ServQual dimensions, with the Reliability dimension having the highest gap (-1.54) and the lowest Empathy dimension (-0.58). The IPA provides results in which seven indicators were identified as priorities for improvement in quadrant I, including adequate parking, sufficient number of staff, simple service procedures, staff ability to provide explanations, staff ability to handle problems, responsiveness in processing complaints, and providing correct answers to customers. In summary, this research confirms operational problems required corrective actions on the prioritized attributes.